A Co-Opted Hormonal Cascade Activates Dormant Adventitious Root Primordia upon Flooding in Solanum dulcamara. Issue 4 (5th February 2016) - Dawood, Thikra; Yang, Xinping; Visser, Eric J.W.; te Beek, Tim A.H.; Kensche, Philip R.; Cristescu, Simona M.; Lee, Sangseok; Floková, Kristýna; Nguyen, Duy; Mariani, Celestina; Rieu, Ivo
Abstract : Soil flooding reactivates dormant adventitious root primordia via ethylene-induced reduction in ABA level. Abstract: Soil flooding is a common stress factor affecting plants. To sustain root function in the hypoxic environment, flooding-tolerant plants may form new, aerenchymatous adventitious roots (AR s), originating from preformed, dormant primordia on the stem. We investigated the signaling pathway behind AR primordium reactivation in the dicot species Solanum dulcamara . Transcriptome analysis indicated that flooding imposes a state of quiescence on the stem tissue, while increasing cellular activity in the AR primordia. Flooding led to ethylene accumulation in the lower stem region and subsequently to a drop in abscisic acid (ABA ) level in both stem and AR primordia tissue. Whereas ABA treatment prevented activation of AR primordia by flooding, inhibition of ABA synthesis was sufficient to activate them in absence of flooding. Together, this reveals that there is a highly tissue-specific response to reduced ABA levels. The central role for ABA in the response differentiates the pathway identified here from the AR emergence pathway known from rice ( Oryza sativa ). Flooding and ethylene treatment also induced expression of the polar auxin transporter PIN2, and silencing of this gene or chemical inhibition of auxin transport inhibited primordium activation, even though ABA levels were reduced. Auxin treatment, however, was not sufficient for AR emergence, indicating that the auxin pathway acts in parallel with the requirement for ABA reduction. In conclusion, adaptation of S. dulcamara to wet habitats involved co-option of a hormonal signaling cascade well known to regulate shoot growth responses, to direct a root developmental program upon soil flooding.